IMPLEMENTATION OF COOPERATIVE LEARNING MODEL STUDENT TEAMS-ACHIEVEMENT DIVISION (STAD) TYPE TO IMPROVE STUDENT COOPERATION IN SOCIAL SCIENCE LEARNING (Classroom Action Research Class VII-D SMP Negeri 1 Bandung) - Yuliawati, Dessy (International Journal Pedagogy of Social Studies, 2017)
Abstract-This study is motivated by the author’s curiosity towards the effectiveness of Cooperative Learning Model Student Teams Achievement Division (STAD) type in improving student cooperation. The purpose of this study is to implementate the Cooperative Learning model Student Teams-Achievement Division (STAD) type to improve student cooperation that includes teamwork in solving problem and doing task, sharing ideas, asking and answering questions, interpersonal communication among students, students and teacher, students and informant, as well as respect for gender, ethnic, race, religion, socioeconomic status, culture and perspective differences. Classroom Action Research (PTK) uses a spiral model by Kemmis and Mc Taggart conducted in three cycles. The subjects of the study are the students of class VII-D. The implementation of learning to improve student cooperation is by implementing the Cooperative Learning model Student Teams-Achievement Division (STAD) Type in Social Science learning. Over three cycles have consistent improvements. In the first cycle, the observation on student cooperation is in the "adequate" category, because the students are lack of interactive communication among students, students and teacher, as well as the students are still lacking in a teamwork. In the second cycle, the result of student cooperation is in the "good" category. In this second cycle, it can be solved by teacher by making improvement and guiding students during teamwork process. In the last cycle, it experienced an increase into the category of "very good", because each student contributes directly or actively in the team. Of this study, it can be concluded that the implementation of Cooperative Learning model Student Teams Achievement Division (STAD) type in Social Science learning can improve student cooperation.Keywords: Cooperative learning STAD type, Cooperation skill, Social science learning